The relationship between bullying and cyberbullying in the university context - Laorden-Gutiérrez, Cristina; Serrano-García, Cristina; Royo-García, Pilar; Giménez-Hernández, Montserrat; Escribano Barreno, Cristina (Pulso. Revista de educación, 2023)
Most research on the relationship between bullying and cyberbullying has focused on educational stages prior to university, especially on secondary education. This study aims to investigate the relationship between bullying and cyberbullying in university students analyzing the connection among roles in the involvement in both phenomena. The sample is made up of 776 university students. They completed the Spanish version of European Bullying Intervention Project Questionnaire (EBIPQ) and European Cyberbullying Intervention Project Questionnaire (ECIPQ) (Ortega-Ruiz et al., 2016), adapted to an online format, which identifies the roles of victim, victimized aggressor and non-involved. Quantitative methodology was used. Results indicates that those students who were classified as being victim or aggressor of bullying were classified in the same way in cyberbullying scale. It is concluded that there is a relationship between being victim of bullying and cyberbullying, on one hand, and being aggressor of bullying and cyberbullying, on the other. The impact for prevention at university is discussed.
Keywords: Bullying; Ciberbullying; Higher Education; Aggresors; Victims